Formation of Complexes Between O Proteins and Replication Origin Regions of Shiga Toxin-Converting Bacteriophages - Kozłowska, Katarzyna; Glinkowska, Monika; Boss, Lidia; Gaffke, Lidia; Deptuła, Jakub; Węgrzyn, Grzegorz (Frontiers in Molecular Biosciences, 2020)
Shiga toxin-converting bacteriophages (or Stx phages) are responsible for virulence of enterohemorrhagic Escherichia coli strains. Although they belong to the group of lambdoid phages, which have served as models in studies on DNA replication mechanisms, details of regulation of replication of Stx phage genomes are poorly understood. Despite high similarity of their replication regions to that of phage lambda, considerable differences occur between them. Here, we present a comparison of origins of replication and O proteins of lambda and selected Stx phages (phages P27 and 933W). Stx initiator proteins, similarly to the lambda O protein, exist in the form of dimers. Only 4 iteron sequences are strongly bound in vitro by the O proteins, despite the presence of 6 such fragments in the Stx ori, while the function of the other two iterons is still crucial for transformation of E. coli wild-type strain by the P27-derived lambdoid plasmid. As these sequences are found in the gene coding for Stx O proteins, the sequences of these proteins themselves are also extended compared to lambda phage. Therefore, proteins O of Stx phages P27 and 933W have 13 additional amino acids. They can act as a space barrier, thus affecting the lesser packing of the O-some Stx complex compared to the structure found in lambda. Such structure of the DNA replication initiation complex may determine its lesser dependence on the processes occurring in the host cell, including transcriptional activation of the origin. Differences between molecular processes occurring during formation of replication complexes in lambda and Stx phages may indicate the specialization of the latter phages and their adaptation to specific environmental conditions where quick genetic switches are crucial.